The application of inelastic neutron scattering to investigate the interaction of methyl propanoate with silica - Cooper, R; McFarlane, A; Geller, H; Silverwood, I; Watkin, D; Parker, S; Winfield, J; Lennon, D (Royal Society of Chemistry, 2016)
A modern industrial route for the manufacture of methyl methacrylate involves the reaction of methyl propanoate and formaldehyde over a silica-supported Cs catalyst. Although the process has been successfully commercialised, little is known about the surface interactions responsible for the forward chemistry. This work concentrates upon the interaction of methyl propanoate over a representative silica. A combination of infrared spectroscopy, inelastic neutron scattering, DFT calculations, X-ray diffraction and temperature-programmed desorption is used to deduce how the ester interacts with the silica surface.